Engineering the Quality in Internet Application for Commerce - Abdullah, Rosmiza Wahida; Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan (2010)
With the proliferation of the Internet, Internet applications are being widely deployed commercially and users are increasingly interacting with them especially for buying and selling activities. For many years, these Internet commerce applications have been successfully adopted in businesses to better serve their online customers. It is therefore very important to identify quality factors that are critical to the success of Internet commerce applications for satisfying customers and businesses. This research aims to contribute to the understanding of quality involved in deploying Internet commerce application. The findings of this study would be useful to business users and web developers as it provides guidance to improve the quality of their Internet commerce. The importance of quality in the Internet applications for commerce needs to be accepted in order to increase business performance.